An insight into predatory journals - Vikas Jaysing Pawar; Jasmine Jawade (Wolters Kluwer Medknow Publications, 2020)
The impact of scholarly journals has increased with invent of Internet due to improved access, faster dissemination, and ease of searching a variety of publications. With the increasing trend of research, open access (OA) publishing has increased intensely over the last few years. The core intent of OA is faster dissemination of research by making it available to readers free of cost. However, some publishers exploited this novel idea for their own benefit. Beall termed them as predatory publishers/journals. In this article, authors have made efforts to understand the predatory publishers/journal, reasons behind their upsurge, their modus operandi, their common targets, and the points which will help readers to identify them. The aim of this article is to expose facts behind the predatory journal and to create awareness among not only budding researchers but also faculty members, authors, and editors about the threat predatory journals carry toward scientific world and to their own curricula.